2016
DOI: 10.1093/ejcts/ezv462
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative follow-up strategy based on recurrence dynamics for non-small-cell lung cancer

Abstract: Our results suggest that the timing of recurrence after surgery for lung cancer is characterized by a bimodal pattern, and the times with the highest risk of recurrence were suggested to differ between men and women. Postoperative follow-up strategies should be based on currently recommended follow-up programmes, take into account the recurrence patterns of lung cancer, and be modified as required to meet the needs of individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 23 publications
3
27
0
4
Order By: Relevance
“…75 LRR after surgery for NSCLC primarily occurs in 2 peaks: the first at 6 to 8 months and the second at 22 to 24 months. 77 An analysis of 74 patients who developed a local recurrence after surgery for stage I NSCLC reported that patients who underwent surgical re-resection survived significantly longer than those who received chemotherapy or radiotherapy, although the 5-year postrecurrence survival rate after repeat surgery remained dismal at only 15%. 78 In a recent study of 40 patients who underwent salvage SBRT for locally recurrent NSCLC that was deemed inoperable, the 18-month OS and local control rates were 77.6% and 87%, respectively.…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%
“…75 LRR after surgery for NSCLC primarily occurs in 2 peaks: the first at 6 to 8 months and the second at 22 to 24 months. 77 An analysis of 74 patients who developed a local recurrence after surgery for stage I NSCLC reported that patients who underwent surgical re-resection survived significantly longer than those who received chemotherapy or radiotherapy, although the 5-year postrecurrence survival rate after repeat surgery remained dismal at only 15%. 78 In a recent study of 40 patients who underwent salvage SBRT for locally recurrent NSCLC that was deemed inoperable, the 18-month OS and local control rates were 77.6% and 87%, respectively.…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%
“…Eine kĂŒrzlich publizierte Studie zeigte innerhalb von diesem Zeitfenster Unterschiede zwischen MĂ€nnern und Frauen [13]. Eine große Auswertung von ĂŒber 2 Millionen Krebspatienten im SEER-Register wurde vor kurzem auf dem amerikanischen Krebskongress ASCO vorgestellt.…”
Section: Caveunclassified
“…The median time from surgery to relapse is 13.9 months for local failure and 12.5 months for distant failure [7]. Moreover, Watanabe et al, in an interesting paper [10], note that there are different recurrence peaks during post-operative follow-up. Indeed, a structured multipeak pattern of recurrence risk has been described, with a bimodal recurrence pattern similar to that in patients with breast cancer.…”
Section: Factors and Patterns Of Recurrence Of Non-small Cell Lungmentioning
confidence: 99%